ICT diffusion as a determinant of human progress*. Issue 4 (2nd October 2017) - Lee, Sang-Oun; Hong, Ahreum; Hwang, Junseok
ABSTRACT: This research poses the question of whether the diffusion of information and communications technology (ICT) in countries can affect human progress. Human progress in this research is defined as progress that allows every member of a society to live in an environment with high economic, political, and civil liberties. To examine the posed question, the authors developed the following three hypotheses. First, ICT diffusion serves as a determinant in human progress. Second, the size of the impact of diffusion of ICT on human progress may differ depending on the income level of the economy. Lastly, the impact of ICT on human progress may differ depending on the type of technological medium. These hypotheses were tested with a sample of 102 countries panel for 14 years from 2000 to 2013 with data from the International Telecommunications Union to see the status of diffusion of ICT, the Heritage Foundation and the Freedom House in order to employ the measure of human progress by a year-lagged seemingly unrelated regression analysis with both pooled and grouped samples. The results suggest that the diffusion of ICT is a determinant of human progress at the global level and that the effects differ depending on the type of technology or the income level of the country.